Opening the 'black box': a multidimensional approach to perceptions of social mobility among black students at the University of Cape Town - Akkurt, O (2014)
This study looks at how individual, social and institutional factors impact perceptions of social mobility among black South African undergraduate students in a previously white institution of higher education, University of Cape Town. In this thesis, a combination of qualitative and quantitative research methods were utilised to explore to what extent higher education mediates the effect of family background on occupation destinations, as perceived by black students. 43 in-depth semi-structured interviews and face-to-face surveys were conducted with black South African students from diverse socio-economic backgrounds. Moreover, a number of semi-structured interviews were conducted with university and state officials on their role in management of transformation at the tertiary level. I demonstrated how black students must navigate their multiple identities in a 'white', 'elitist' university. I also presented the ways in which these identities were challenged or rewarded by peer groups and the university’s socio-cultural realm. The idea that education is not simply one abstract force mediating the effect of family background on occupation destinations, as perceived by students, is central to the argument of this thesis. I argue that the social mobility literature must incorporate social and institutional processes at the tertiary level into its analysis of intergenerational mobility.